Evaluation of interferon gamma release assay using Mycobacterium tuberculosis antigens for diagnosis of pulmonary tuberculosis in bcg vaccinated population of Kelantan, Malaysia - Ahmad, Hajar Fauzan (2013)
Although Malaysia is an intermediate tuberculosis (TB) burden country, the absolute number of new cases has been increasing recently. Improvement in early diagnosis followed by efficient chemotherapy is the major control strategy for TB. Currently, T-cell based interferon-gamma release assays using Mycobacterium tuberculosis (MTB) antigens from QuantiFERON4-TB Gold In-Tube (QFT-GIT) assays have shown unclear values in terms of sensitivity and specificity in the diagnoses of active pulmonary and latent TB infections. For this study, two MTB antigens known as VacIII and Ubi-VacIII were evaluated for their diagnostic potential based on dynamic T-cell responses among BCG-vaccinated populations were investigated. Thirty-six patients with active pulmonary TB and 38 healthy controls (FIC) from a selected hospital in Kelantan, Malaysia were recruited and tested by using gold standard assays and IGRA. The sensitivity and specificity of QFT-GIT, VacIII and Ubi-VacIII antigens among BCG vaccinated population were 30.4% and 88.9%, 47.8% and 55.6%, and 30.4% and 18.5%, respectively. Even though the overall agreement between IGRA and the gold standards assays showed fairly poor correlation (K-values=0.320), the T-cell responses against the antigens were considered statistically significant (/><0.001). In conclusion, all the 3 antigens were unable to discriminate between TB and HC due to high variability of the sensitivities and specificities they demonstrated. As compared to VacIII and Ubi- VacIII, QFT-GIT showed better specificity however its low sensitivity was expected due to the fact that the TB7.7 antigen is absent in clinical MTB strains of South East Asia.